EFEKTIVITAS BIBLIOTHERAPY UNTUK MENGURANGI KECEMASAN PADA PENDERITA KANKER - Maydiana, Tauristia; siswanto, Siswanto (Universitas Katolik Soegijapranata, 2012)
The aim of this research is to know the affectivity of bibliotherapy to reduce anxiety of cancer patients. The hypothesis is there is differentiation before and after bibliotherapy treatment among cancer patients. The anxiety decreases after bibliotherapy treatment. This research uses Single-Case Experimental Design (quasi experiment). Subjects are 1m? female patients with cervix and uterus cancers. There are J 5 sessions, including bibliotherapy treatment 9 sessions. Result shows that there are decreasing anxieties toward their cancers among the subjects. There are differentiations between anxiety scale (Hamilton anxiety scale and Death anxiety scale). After the bibliotherapy treatment, posttest scores are decreasing compared with the pretest scores